Measuring cognitive flexibility: A brief review of neuropsychological, self-report, and neuroscientific approaches - Hohl, Kelly; Dolcos, Sanda (Frontiers in Human Neuroscience, 2024)
Cognitive flexibility involves dynamic processes that allow adaption of our thinking and behavior in response to changing contextual demands. Despite a large consensus about its beneficial effects, cognitive flexibility is still poorly understood. In this mini review, we examined the main conceptualizations and approaches for assessing cognitive flexibility: 1) neuropsychological tasks, 2) self-report questionnaires, and 3) neuroscientific approaches. The reviewed evidence shows that the definition and assessment of cognitive flexibility are not unified within the field and suggests that a more consensual and consistent conceptualization and operationalization of this important concept is needed. We propose that an integrative behavior-brain-context approach can help advance our understanding of cognitive flexibility.